2023
DOI: 10.1186/s13037-023-00360-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of errors related to surgical pathology specimens of different hospital departments with a patient safety approach: a case study in Iran

Abstract: Background Most surgical specimen errors occur in the pre-analysis stage, which can be prevented. This study aims to identify errors related to surgical pathology specimens in one of the most comprehensive healthcare centers in Northeast Iran. Methods The present study is descriptive and analytical research conducted cross-sectionally in 2021 at Ghaem healthcare center in the Mashhad University of Medical Sciences on the basis of a census sampling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Tabatabaee et al emphasized that training nurses, adopting an evidence-based care approach and creating interaction and coordination between nurses and pharmacists in the hospital can play an effective role in reducing the medication error of nurses [ 15 ]. Also Promoting patient safety culture can effectively reduce the medical errors [ 34 ]. Eliminating redundancies and traditional actions with effective interaction was one of the effective solutions that was associated with increasing the satisfaction of the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabatabaee et al emphasized that training nurses, adopting an evidence-based care approach and creating interaction and coordination between nurses and pharmacists in the hospital can play an effective role in reducing the medication error of nurses [ 15 ]. Also Promoting patient safety culture can effectively reduce the medical errors [ 34 ]. Eliminating redundancies and traditional actions with effective interaction was one of the effective solutions that was associated with increasing the satisfaction of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoudi et al reported a high prevalence of errors in medical centers [ 19 ]. So, The patient safety culture in the hospital is inappropriate and requires urgent intervention [ 34 ] and there is a need for more studies in this field to achieve a medical care system with the highest standards [ 35 ]. Therefore, the current research was carried out with the aim of improving safety in gastroenterology departments.…”
Section: Introductionmentioning
confidence: 99%